Korean Transnational Students’ School Adjustment: An Ecological Perspective - Hyeyoung Kang; Hoe Kyeung Kim (Middle Grades Review, 2017)
This research explored Korean early study abroad students’ school adjustment in the U.S., as well as how their microsystems (family, peer, school) affect their experiences. To understand their experience, we posed two research questions: 1) What are Korean early study abroad students’ experience like in adjusting to American middle schools? and 2) How do these students’ microsystems (family, peer, and school) affect their experiences in the process of adjustment? Four Korean early study abroad students participated in a collective case study. Each student was interviewed three times and observed in both their content area and ESL classes. All students described tremendous challenges in adjusting to their new school in the U.S. Specifically, their challenges were pertaining to different aspects of learning experiences as well as school belonging. While their limited English proficiency was a primary factor in these challenges, a lack of support from their peers, parents, teachers and school also seemed to affect their school adjustment. Moreover, findings indicated disconnections among their microsystems, contributing to a lack of support in their school adjustment.
Keywords: Transnational students; School adjustment; Ecological theory; Korean early study abroad students